РЕГУЛЮВАННЯ ЧАСТОТИ І НАПРУГИ В АВТОНОМНИХ СИСТЕМАХ ЕЛЕКТРОЖИВЛЕННЯ З ПАРАЛЕЛЬНО ПРАЦЮЮЧИМИ ГЕНЕРАТОРАМИ ЗМІННОГО СТРУМУ З ВИКОРИСТАННЯМ МЕТОДУ ПІДТРИМКИ ВЕДУЧОГО ГЕНЕРАТОРА - Мазуренко, Л.І.; Джура, О.В.; Шихненко, М.О.; Коцюруба, А.В. (Інститут електродинаміки НАН України, Київ, 2023)
Such methods of regulating voltage and frequency in isolated power systems with AC electric generators as droop method, curve shifting method and master-slave method were primarily developed for synchronous generators based systems. In modern power systems induction generators, regulated dump loads, energy storage devices with AC/DC and AC/DC/AC power converters, etc. are used in addition to synchronous generators. The investigation of new configurations of power systems is closely tied with further development of control methods for load sharing and new controllers for voltage and frequency regulation of the systems. The article reviews simple-to-implement known control methods used for isolated power systems with parallel operated synchronous generators and proposes a master-generator assistance method for power systems with parallel operated synchronous and induction generators, static var compensators, dump loads and energy storage devices with interface power converters. The system “Hydroelectric unit with a synchronous generator - dump load - hydroelectric unit with an induction generator - compensating capacitors - transformer – AC local load" is considered and two techniques for regulation of electric frequency and voltage magnitude in the specified system are presented with accordance to the statements of the proposed method. The proposed control algorithm of the dump load frequency controller is in agreement with the control algorithm of the speed controller of the master unit. The functions assigned to the electronic PID speed controller of the master unit are to maintain the electric frequency in the system equal to nominal value and regulate the active power sharing. Verification of the proposed control algorithms for isolated electric power systems was carried out. References 23, figures 5, table 1.